PEMANFAATAN MEDIA SOSIAL UNTUK MENGEMBANGKAN PESONA CANDI IJO SEBAGAI WISATA BERSEJARAH - Yanuar Satrhio Insanaputra (Kepariwisataan: Jurnal Ilmiah, 2022)
In Yogyakarta, there are many temples scattered in various places, Candi Ijo is one of them. This temple, is a Hindu-style temple complex that has a lot of historical value in it, from places of worship to rulers of that era has a relationship with Candi Ijo. Therefore, it is necessary to have a place to collect this information, so that it is easily accessible to potential tourists. The growth of the internet makes information available, making it easier for tourists to find information about the area to be visited. One of them is using social media, which is now widely used by the public to get information.